Evidence of High Mortality and Increasing Burden of Sepsis in a Regional Sample of the New Zealand Population. (24th August 2017) - Huggan, Paul J; Bell, Anita; Waetford, James; Obertova, Zuzanna; Lawrenson, Ross
Abstract: Background: Sepsis is a life-threatening complication of infection. The incidence of sepsis is thought to be on the increase, but estimates making use of administrative data in the United States may be affected by administrative bias. Methods: We studied the population-based incidence of sepsis in the Waikato region of New Zealand from 2007 to 2012 using International Classification of Diseases, Tenth Revision, Australian Modification, which lacks a specific code for sepsis. Results: Between 2007 and 2012, 1643 patients met coding criteria for sepsis in our hospitals. Sixty-three percent of patients were 65 or over, 17% of cases were admitted to an intensive care unit, and the in-hospital and 1-year mortality with sepsis was 19% and 38%, respectively. Age-standardized rate ratios (ASRRs) demonstrated that sepsis was associated with male sex (ASRR 1.4; 95% confidence interval [CI], 1.23–1.59), Maori ethnicity (ASRR 3.22 compared with non-Maori; 95% CI, 2.85–3.65), study year (ASRR 1.62 comparing 2012 with 2008; 95% CI, 1.18–2.24), and socioeconomic deprivation (ASRR 1.72 comparing the highest with the lowest quintile of socioeconomic deprivation; 95% CI, 1.5–1.97). Multiorgan failure was present in approximately 20% of cases in all age groups. Intensive care unit admission rate fell from 30% amongst 25- to 34-year-olds to less than 10% amongst those aged 75 and over. Conclusions: In a 9% sample of the New Zealand population, the incidence of sepsis increased by 62% over a 5-year period. Maori, elderly, and disadvantaged populations were most affected.